Filler Utterances of Instructors in ELT Context - Aloisius Wisnu Mahendra; Barli Bram (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
This study investigated filler utterances produced by English instructors teaching a general English course considering that fillers play crucial roles in English language teaching (ELT) contexts. Data, consisting of 981 filler utterances, were collected from recorded teaching sessions conducted by female and male English instructors at the Language Institute of Sanata Dharma University, Yogyakarta, Indonesia. The collected data, in the form of transcribed texts containing instructors’ filler utterances, were examined with the discourse analysis method. The findings showed that the female instructors produced more types of fillers with the total of 639 utterances and the male ones 342. Fourteen types of phrase fillers uttered by the female instructors were as follows: actually, alright, and then, anyway, I guess, I mean, I think, okay, right, so, well, ya (yes), you know, and you see. Thirteen kinds of phrase fillers identified among the male instructors’ utterances were alright, and now, and then, anyway, I guess, I mean, I think, okay, right, so, well, ya (yes), and you know. The frequently identified fillers shared benefits in terms of introducing topics, getting the students’ attention, giving instructions, searching for words, and emphasizing and confirming ideas.